Ankyloglossia: Surgical management and functional rehabilitation of tongue - Shadab Khan; Shweta Sharma; Vivek Kumar Sharma (Wolters Kluwer Medknow Publications, 2017)
Ankyloglossia or "tongue-tie" is a rare congenital anomaly characterized by an abnormally short, thick, fibrosed lingual frenulum which may cause restriction in function of tongue including limitation in tongue movement. The lingual frenulum may be fibrous or muscular, and the tie may be complete or partial. Most often, ankyloglossia is seen as an isolated condition in an otherwise normal individual. This article reports the surgical management of a 20-year-old patient having ankyloglossia associated with restricted movement of tongue and difficulty in speech. The treatment involved is surgical removal of the lingual frenum followed by tongue training exercise and speech therapy to functionally rehabilitate the tongue. Six months postoperatively, the patient showed uneventful healing and was satisfied with the procedure.